Penerapan Model Kooperatif Tipe Mood, Understand, Recall, Digest, Expand, Review (Murder) untuk Meningkatkan Hasil Belajar Mata Pelajaran IPS: Penelitian Tindakan Kelas di Kelas VIII-8 SMP Negeri 138 Jakarta - Putri, Nuraini Eka; Siswono, Eko (Edukasi IPS, 2019)
This study aims to determine whether the application of Mood, Understand, Recall, Digest, Expand, Review (MURDER) learning model can improve learning outcomes IPS students VIII-8 SMP Negeri 138 Jakarta first semester of the 2018/2019 Lesson Year from October to November 2018. The method used in this research is Action Research Class (PTK). This study uses three cycles, and each cycle consists of four stages: Planning Action, Action Acting, Observation, and Reflection. Based on the results of thestudy of the learning results have increased in each cycle, the one cycle of 34% (13 students) obtained the value of learning outcomes above KKM 73, cycle two 61% (22 students) reaches above KKM 73, and the third cycle 86% (31 students) reached the score above KKM 73. In addition, the success of the increase also occurred in the implementation of the activity of asking, answering, arguing, and solving the problem in the Thus it can be concluded that the application of Mood, Understand, Recall, Digest, Expand, Review (MURDER) learning model can improve learning outcomes of IPS learners and can improve the learner activity, so that learners can get better IPS learning outcomes that are above KKM standard 73.